On the rationing the parameters of asymmetric loading of all-purpose freight cars - A. M. BRZHEZOVSKIY (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
Due to the presence in the operating fleet of freight cars with a base of over 10 m, as well as the practical impossibility of symmetrically placing loads with a weight corresponding to the nominal carrying capacity on open rolling stock, adjustments to the existing asymmetrical loading standards are necessary. To this end, it is proposed to apply a comprehensive methodology for determining the allowable parameters of asymmetrical placement of freights, based on a combination of strength criteria of the bearing elements of cars, ensuring the normative level of dynamic qualities and stability of the loaded car. The article provides an example of determining the permissible parameters of the joint lateral and longitudinal displacement of the total center of gravity of the car (ЦТгр°), loaded to the nominal capacity. According to the results of the studies to determine the allowable values of longitudinal and lateral displacement ЦТгр° with unbalanced placement within the loading platform of the car, including the presence of a joint displacement, it was found that to improve the efficiency of using freight cars with an increased base, it is advisable to update the current offset standards of ЦТгр°. It is recommended to take the values of longitudinal displacement ЦТгр° for cars with a body base of 14.6 and 19.0 m respectively 1.46 and 2.11 m for freight with a total weight of 50 tons; 1.10 and 1.43 m for freight with a total weight of 60 tons; 0.22 and 0.28 m – for freight with a total weight of 67 tons. When placing freights with a total weight of over 67 tons with a height of center of gravity of 2.0–2.2 m on 4-axle freight cars with an axle load of 230.5 kN without limiting the permissible driving speeds, it is recommended to use a graphical method for determining the joint (longitudinal and transverse) displacement ЦТгр°. With an increase in the joint displacement parameters ЦТгр°, it will be necessary to limit the speed of the car in the curved sections of the track and to the lateral direction on the turnouts.